Global biogeography of marine amphipod crustaceans: latitude, regionalization, and beta diversity - Arfianti, Tri; Costello, Mark J (Marine Ecology Progress Series, 2020)
Studying the biogeography of amphipod crustaceans is of interest because they play an important role at lower trophic levels in ecosystems. Because they lack a planktonic larval stage, it has been hypothesized that marine benthic amphipod crustaceans may have short dispersal distances, high endemicity, and spatial turnover in species composition, and consequently high global species richness. In this study, we examined over 400000 distribution records of 4876 amphipod species, and identified 12 regions of endemicity. The number and percent of endemic species peaked at 30°-35°S and coincided with 3 of these regions of high endemicity: Australia, New Zealand, and southern Africa. Pelagic species of marine amphipod crustaceans were more cosmopolitan than benthic species. The latitudinal patterns of richness (alpha, gamma, and ES50) and species turnover were at least bimodal. Most occurrence records and greater alpha and gamma richness were in mid-latitudes, reflecting sampling bias. Both ES50 and beta diversity had similar richness in the tropics, mid-latitudes, and on the Antarctic shelf around 70°S. These 2 indices exhibited a sharp dip in the deep Southern Ocean at 55°S. ES50 peaked at 30°-35°S and a small dip was apparent near the equator at 5°-10°N. Beta diversity was driven mostly by turnover rather than nestedness. These findings support the need for conservation in each realm of species endemicity and for amphipods, particularly in Antarctica and the coastal mid-latitudes (30°-35°S) of the Southern Hemisphere. KEYWORDS: Endemicity · Latitudinal gradients · Conservation · Species richness · Species turnover
Keywords: Sørishavet; biogeografi; crustacea; krepsdyr; marin biologi; marine økosystemer; zoogeografi

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking

Growth-related changes in salt gland mass in gentoo and chinstrap penguin chicks - Kim, Youmin; Jeong, Min-Su; Seo, Hae-Min; Kim, Hankyu; Lee, Woo-Shin; Choi, Chang-Yong (Polar Research, 2020)
The salt gland is a well-developed osmoregulation organ in marine birds, and its relative size often reflects an individual’s feeding environment and osmoregulation capability. The development and functions of salt glands have been described for the Adélie penguin (Pygoscelis adeliae), but this information has been poorly documented in the other two pygoscelid species: gentoo (P. papua) and chinstrap penguins (P. antarcticus). To describe the growth-related changes in salt gland masses in relation to chick growth, we measured the wet mass of the salt glands collected from dead gentoo and chinstrap chicks during the early breeding period. The mass of the salt glands was linearly proportional to their body measurements, especially to body mass, in both species, and no significant difference was detected between the two species. Penguins are obligate marine dwellers throughout their life cycle, and the development of the salt gland in penguin chicks suggests that their ability to regulate dietary osmotic stress begins at an early stage of development after hatching. Furthermore, the linear relationship between the gland mass and body mass also suggests that the osmoregulation capability may continue to develop as penguin chicks grow. This descriptive note provides novel and quantitative information on the early developmental pattern of salt glands in gentoo and chinstrap penguins.
Keywords: Antarktis; marine økosystemer; ornitologi; osmoregulering; osmotisk stress; pingviner; saltkjertel; zoologi

Calving Event Led to Changes in Phytoplankton Bloom Phenology in the Mertz Polynya, Antarctica - Liniger, Guillaume; Strutton, Peter G.; Lannuzel, Delphine; Moreau, Sebastien (Journal of Geophysical Research: Oceans, 2020)
Polynyas are subject to variability in winds and ocean circulation and are important sites of ecological productivity. In February 2010, the B09B iceberg collided with the Mertz Glacier Tongue (MGT), calving a 78 × 40-km giant iceberg which modified the icescape and primary productivity of the Mertz polynya. In this study, we use satellite ocean color and sea ice concentration to investigate the variability, trends, and drivers of phytoplankton blooms in the Mertz polynya since 1997. During the bloom, over 21 years, we found (i) a later ice retreat time, (ii) an increase in sea ice concentration, (iii) a decrease in open-water period, (iv) a later bloom start, and (v) a decrease in bloom duration. Our results suggest that major postcalving changes in the physical characteristics of the polynya, mainly its icescape, are the primary drivers of phytoplankton phenology. More specifically, the MGT calving event resulted in significant seasonal and regional changes, with higher eastern chl-a and mean summer chl-a postcalving. While satellite data are useful to study long-term variability in these inhospitable areas, they only focus on the ocean surface and are obscured by ice and clouds. Additional subsurface parameters from seal tags, gliders and moorings in the southernmost polar regions would strengthen our comprehension of phytoplankton and physical changes in ocean dynamics that may have far-reaching consequences, from global circulation to carbon export.
Keywords: Sørishavet; fytoplankton; havsirkulasjon; isbre; kalving; marin biologi; marine økosystemer; oseanografi; polynja